Lifestyle Medicine and the Management of Cardiovascular Disease. - Doughty, Kimberly N; Del Pilar, Nelson X; Audette, Amanda; Katz, David L (Current cardiology reports, 2017)
PURPOSE OF REVIEW: Evidence has clearly demonstrated the importance of lifestyle factors (e.g., diet, physical activity, smoking) in the development of cardiovascular disease (CVD). Interventions targeting these behaviors may improve outcomes for CVD patients. The aim of this review is to summarize the effects of lifestyle interventions in individuals with established CVD., RECENT FINDINGS: Most recent trials focused on diet, physical activity, stress reduction, or a combination of these. Findings were mixed, but most interventions improved at least some markers of cardiovascular risk. Few studies measured long-term clinical outcomes, but some suggested a possible benefit of stress reduction and multifaceted interventions on cardiovascular events. The benefits of lifestyle change for CVD patients have been established by decades of evidence. However, further research is needed to determine the optimal intensity, duration, and mode of delivery for interventions. Additional studies with long-term follow-up and measurement of clinical outcomes are also needed.
52 citations (Crossref) [2023-10-31] Place: United States Doughty, Kimberly N. Yale-Griffin Prevention Research Center, 130 Division Street, Derby, CT, 06418, USA. Del Pilar, Nelson X. San Juan Bautista School of Medicine, Caguas, PR, USA. Audette, Amanda. Department of Public Health, Southern Connecticut State University, New Haven, CT, USA. Katz, David L. Yale-Griffin Prevention Research Center, 130 Division Street, Derby, CT, 06418, USA. davkatz7@gmail.com.
Keywords: *Cardiovascular Diseases; *Healthy Lifestyle; Cardiovascular Diseases; Cardiovascular Diseases/pc [Prevention & Control]; Cardiovascular Diseases/px [Psychology]; Diet; Disease Management; Exercise; Healthy Lifestyle; Humans; Life Style; Lifestyle; Mediterranean diet; Physical activity; Review; Stress reduction; aerobic exercise; cardiovascular disease; cardiovascular risk; dept.pch; disease management; evidence based medicine; follow up; healthy lifestyle; human; lifestyle; lifestyle modification; outcome assessment; physical activity; psychology; risk reduction; stress; therapy effect